2014
DOI: 10.1002/2014jc009985
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal changes in snow depth on Arctic sea ice

Abstract: Snow plays a key role in the growth and decay of Arctic sea ice. In winter, it insulates sea ice from cold air temperatures, slowing sea ice growth. From spring to summer, the albedo of snow determines how much insolation is absorbed by the sea ice and underlying ocean, impacting ice melt processes. Knowledge of the contemporary snow depth distribution is essential for estimating sea ice thickness and volume, and for understanding and modeling sea ice thermodynamics in the changing Arctic. This study assesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
249
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(263 citation statements)
references
References 43 publications
13
249
1
Order By: Relevance
“…Snow data from the IMB buoy at the 2011 site indicate that snow depths did not increase significantly after the March measurements were taken, showing <5 cm accumulation for April and May combined ( Figure 5). The lack of snow accumulation is consistent with the results of Webster et al [2014], which show low April and May snow accumulation rates in this region from more recent years.…”
Section: Influence Of Snow Distribution On Melt Pond Formationsupporting
confidence: 90%
See 1 more Smart Citation
“…Snow data from the IMB buoy at the 2011 site indicate that snow depths did not increase significantly after the March measurements were taken, showing <5 cm accumulation for April and May combined ( Figure 5). The lack of snow accumulation is consistent with the results of Webster et al [2014], which show low April and May snow accumulation rates in this region from more recent years.…”
Section: Influence Of Snow Distribution On Melt Pond Formationsupporting
confidence: 90%
“…Especially evident on undeformed first-year ice, the lateral spread of meltwater can cause maximum pond fractions as high as 70% due to the low surface topography of snow drift bed forms [Scharien and Yackel, 2005;Petrich et al, 2012a;Polashenski et al, 2012]. On a broader scale, Webster et al [2014] have shown that snow depth distributions on both ice types in the western Arctic have decreased, and may have two effects on melt pond formation (1) more thinly snow-covered ice and bare ice may expose the ice surface to solar radiation earlier in the season and hasten melt, and (2) less freshwater may be available during early pond formation to form low-salinity ice surface layers [Eicken et al, 2002], which further motivates an analysis of seasonal melt pond evolution on drifting sea ice in more recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The Arctic sea-ice cover is declining rapidly, with reductions in the summer minimum extent by more than 50%, a decline in mean thickness by over 60%, and a 30-60% decrease in snow on ice thickness since the 1970s (Stroeve et al 2012;Webster et al 2014;Lindsay and Schweiger 2015). These changes in sea-ice allow for more light penetration and longer growing seasons (Wassmann and Reigstad 2011;Nicolaus et al 2012), potentially increasing Arctic Ocean primary production (Arrigo et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is closely connected with the thinning of the sea ice (Kwok and Rothrock, 2009;Kwok and Cunningham, 2015;Wadhams, 2012) and the change in the ice age distribution with less MY ice and more FY ice (Tschudi et al, 2016). Later onset of freeze (Stroeve et al, 2014) and correspondingly later start of snow accumulation is the last but 15 not the least factor that determine snow depth distribution in present time (Wang et al, 2013;Webster et al, 2014).…”
Section: Resultsmentioning
confidence: 89%
“…In the case of FY ice, snow accumulation can only start after the sea ice freezing is stable. A delayed sea ice freeze-up will lead to a delayed start of snow accumulation and thereby have 5 impact on the snow depth evolution during the winter (Webster et al, 2014). From the Sever data an empirical relation between ice thickness and snow depth can be derived for FY ice, using least square regression, resulting in the equation: = 0.069 * ℎ + 2.0 where SD is snow depth of the undisturbed snow on the undeformed ice and Ice_th is ice thickness of the FY ice (in cm), using a threshold of 200 cm, as shown in Fig.…”
Section: Depth Of Undisturbed Snow Covermentioning
confidence: 99%